2023
DOI: 10.4236/health.2023.152013
|View full text |Cite
|
Sign up to set email alerts
|

Review of Factors Associated with Depression among Pregnant Women during the COVID-19 Pandemic

Abstract: Purpose: This purpose of the study was to investigate the factors both risk and protective associated with depression among pregnant women during the coronavirus disease (COVID-19) pandemic. Methods: A literature search was conducted on July 2022, through PubMed, CINAHL, MEDLINE, CiNii, and the Japan Medical Abstract Society databases, with the keywords "COVID-19", "pregnant women", and "depression". The titles/abstracts were screened based on three selection criteria: 1) inclusion of pregnant women; 2) descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The risk factors associated with depression among pregnant women during COVID-19 were "distress from COVID-19-related experiences", "reduced/low income", "unemployment", "anxiety", "history of mental illness", "lack of social support", and "reduced/lack of exercise". However, protective factors associated with pregnant Japanese women were not reported [8]. Studies of pregnant women during the COVID-19 pandemic predicted the potential association of prenatal depression and anxiety with postpartum depression [9].…”
Section: Introductionmentioning
confidence: 99%
“…The risk factors associated with depression among pregnant women during COVID-19 were "distress from COVID-19-related experiences", "reduced/low income", "unemployment", "anxiety", "history of mental illness", "lack of social support", and "reduced/lack of exercise". However, protective factors associated with pregnant Japanese women were not reported [8]. Studies of pregnant women during the COVID-19 pandemic predicted the potential association of prenatal depression and anxiety with postpartum depression [9].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, regarding pregnancy and childbirth, there were cases including classes during pregnancy, family presence during childbirth, cancellation or restriction of postnatal visits, abandonment of return to parents' home after childbirth, and cancellation of infant health checkups [5] [6] [7]. Furthermore, it has been reported that approximately 24% women may have experienced postnatal depression [8], and psychological anxiety increases significantly [9] [10] [11].…”
Section: Introductionmentioning
confidence: 99%